Effects of biogenic volatile organic compounds and anthropogenic NOx emissions on O3 and PM2.5 formation over the northern region of Thailand - Uttamang, Pornpan; Janta, Radshadaporn; Bran, Sherin Hassan; Macatangay, Ronald; Surapipith, Vanisa; Tala, Wittaya; Chantara, Somporn (Frontiers in Environmental Science, 2023)
Biogenic volatile organic compounds (BVOC), which are mainly emitted from plants, are a major precursor for the formation of ground-level ozone (O3) and secondary organic aerosols (SOA). In the northern region of Thailand, 63.8% of the land area is covered by forests. Herein we investigated the effects of biogenic volatile organic compounds (BVOC) emitted from plants and anthropogenic NOx emissions on ground-level ozone (O3) and fine particulate matters (PM2.5) formation. The Weather Research and Forecasting Model coupled with Chemistry (WRF-Chem Model) was applied to simulate three scenarios including baseline, noBio and modiAntho simulations. The modeling results over the northern region of Thailand indicate that BVOC emissions over the northern region of Thailand contributed only 5.3%–5.6% of the total concentrations of PM2.5 and BVOC had a direct relationship to glyoxal and SOA of glyoxal. The comparison between the observed and the modeled isoprene over the study site showed an underestimation (3- to 4-folds) of the simulated concentrations during the study period (June and November 2021). In June, decreases in anthropogenic NOx emissions by 40% led to PM2.5 reductions (5.3%), which corresponded to a zero BVOC emission scenario. While higher PM2.5 reductions (5.6%) were found to be caused by anthropogenic NOx reductions in November, small increases in PM2.5 were observed over the area near a power plant located in Lampang Province. Therefore, both VOC and NOx emission controls may be necessary for areas near the lignite mine and power plant. Since the areas within the vicinity of the power plant were under VOC-limited regimes, while the other areas were determined to be NOx-limited.